Effect of Different Organic Manures Application on the Bioactive Compound and Yield of Taşköprü Garlic (Allium sativum L.) under 50% Drought - TURFAN, Nezahat (Uluslararasi Tarim ve Yaban Hayati Bilimleri Dergisi, 2021)
This study was carried out to assess the contribution of different organic fertilizer mixtures [(CONTROL (open field), CATTLE, CHICKEN, GOAT, İMPORTED PEAT (IPT), NATİVE PEAT (NPT), FİELD SOİL (FS: in greenhouse)] to drought tolerance of Taşköprü garlic, which was exposed to 50% water deficiency under greenhouse conditions. For this purpose, the measurement of yield was performed with bulbs, but the amount of some bioactive chemicals as chlorophyll, carotenoid, flavonoid, phenolic, proline, protein, free amino acid, sugars, pyruvic acid, malondialdehyde (MDA), hydrogen peroxide (H2O2), ascorbate peroxidase (APX) and superoxide dismutase (SOD) activities obtained from the fresh leaf and cloves grown in the different soil mix. According to the result, while the amount of pigment was found to be higher in the leaf of FS and FS-IPT, the flavonoid in FS-CHICKEN and total phenolic in FS-CATTLE-GOAT samples, nitrogenous compounds, and sugars (glucose, sucrose) were found to be rich in the control group (open field). The measurement of bulb weight, length, diameter, and the amount of lycopene, flavonoid, total phenolic, and free amino acid of garlic cloves obtained from FS-CHICKEN-IPT, FS-CATTLE-GOAT, FS-CHICKEN-GOAT, and FS-GOAT-NPT was higher when compared to the control. Furthermore, APX and SOD increased, whereas malondialdehyde lowered in these samples. As a result, the amounts of bulb yield, enzymatic and non-enzymatic compound, and sugars estimated using organic fertilizer were higher than the control, which was grown with inorganic fertilizer in an open field. In addition, the most drought-susceptible examples are the samples of FS, FS-ITP, FS-NTP, and FS-CATTLE soils considering all data.
Keywords: 2. Zero hunger; 15. Life on land; 6. Clean water; 3. Good health